2005
DOI: 10.1523/jneurosci.4560-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Aneuploidy in the Normal Human Brain

Abstract: Together, these data demonstrate that human brain cells (both neurons and non-neuronal cells) can be aneuploid and that the resulting genetic mosaicism is a normal feature of the human CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
251
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(266 citation statements)
references
References 28 publications
11
251
3
1
Order By: Relevance
“…This observation is in agreement with a recent single-neuron sequencing study that, despite identifying a high frequency of subchromosome copy number variants, did not observe high levels of whole-chromosome aneuploidy in neurons (30). Prior reports used SKY and FISH to assess the prevalence of aneuploidy and found it to exceed 50% and 20% in the liver and brain, respectively (13,14,(16)(17)(18)(19)(20). We attribute this difference to drawbacks associated with using FISH to detect somatic aneuploidy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is in agreement with a recent single-neuron sequencing study that, despite identifying a high frequency of subchromosome copy number variants, did not observe high levels of whole-chromosome aneuploidy in neurons (30). Prior reports used SKY and FISH to assess the prevalence of aneuploidy and found it to exceed 50% and 20% in the liver and brain, respectively (13,14,(16)(17)(18)(19)(20). We attribute this difference to drawbacks associated with using FISH to detect somatic aneuploidy.…”
Section: Discussionsupporting
confidence: 91%
“…We conclude that the prevalence of aneuploidy in the adult human brain is 2.2% (95% CI 0.3%-7.9%; Fig. 2B and Table S1), significantly less than the more than 20% aneuploidy reported by prior studies (16)(17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In the literature, there are contrasting data on chromosomal stability of nonimmortalized NSC lines and some data indicate that, at least for adult mouse SVZ stem cells in vivo, chromosomal abnormalities might actually be somehow expected. [28][29][30][31][32][33] Although preliminary, these results indicate that the chromosomal instability described by a number of authors for both adult mouse SVZ-derived neurosphere 8,20 and adult rat hippocampal progenitor 17 cultures is also present in aNS-1 cells. Further analyses are required to better define when these aberrations arise in the aNS cultures and how they evolve with time.…”
Section: Discussionsupporting
confidence: 51%
“…For somatic tissues, an important part of the knowledge on mosaicism has been obtained from studies using cytogenetic banding techniques, which provide information on whole chromosome copy number or large aberrations, and fluorescent in situ hybridization (FISH), studying a single locus. These studies have shown that the grade of mosaicism varies from tissue to tissue and the percentage of aneuploid cells increases with age, but provide limited insight on the occurrence of small genetic imbalances [2][3][4][5] . More recently, the group of Abyzov et al 6 made use of the clonal nature of humaninduced pluripotent stem cells (hiPSCs) to show that human skin fibroblasts are highly mosaic, with up to 30% of cells carrying copy number variants (CNVs).…”
mentioning
confidence: 99%